Cd(II) retention and remobilization on δ-MnO2 and Mn(III)-rich δ-MnO2 affected by Mn(II). (September 2019) - Sun, Qian; Cui, Pei-Xin; Zhu, Mengqiang; Fan, Ting-Ting; Ata-Ul-Karim, Syed Tahir; Gu, Jia-Hui; Wu, Song; Zhou, Dong-Mei; Wang, Yu-Jun
Abstract: Birnessite owing to its negative surface charge and defective structure exhibits high sorption affinities for Cd(II). However, Mn(II) can not only compete for the sorption sites with Cd(II), but also react with structural Mn(IV) in birnessite to form Mn(III), and thus, affect Cd(II) immobilization by birnessite. Herein, we investigate effects of Mn(II) on Cd(II) retention and remobilization on two birnessite δ-MnO2 and Mn(III)-rich δ-MnO2 (denoted as HE-MnO2 ). At pH 5.5, Cd(II) sorption to birnessite was inhibited by Mn(II) addition. Mn(II) addition to δ-MnO2 led to Cd(II) migration from vacant sites to edge sites, forming double-corner sharing (DCS) complexes. Mn(II) introduction to δ-MnO2 led to less stable Cd(II) species formed on birnessite, indicating that Cd(II) was more firmly bound to vacant sites than edge sites of birnessite. Cd(II) formed double-edge sharing (DES) and DCS complexes on HE-MnO2 . Mn(II) addition to HE-MnO2 increased the CdMn distance in DES complexes. The stability of adsorbed Cd(II) on HE-MnO2 was slightly elevated due to Mn(II) addition. At pH 7.5, Mn(II) had no effect on Cd(II) sorption and desorption amounts on birnessite. However, low concentration of Mn(II) added to δ-MnO2 induced partial migration of Cd(II) from vacant sites to edge sites while high concentration of Mn(II) added to birnessite led to the formation of amorphous Cd(II)-Mn(III) coprecipitate. These findings imply that aqueous Mn(II) is an important factor in influencing Cd(II) immobilization by birnessite in the environment. Graphical abstract: Unlabelled Image Highlights: Mn(II) addition to δ-MnO2 led to Cd(II) migration from vacant sites to edge sites. Mn(II) introduction to δ-MnO2 led to less stable Cd(II) species formed on birnessite. Cd(II) formed edge sharing and cornering sharing complexes on Mn(III)-rich δ-MnO2 regardless of Mn(II) addition. Cd(II) was more firmly bound to vacant sites than edge sites of birnessite. High concentration of Mn(II) added to birnessite led to the formation of amorphous Cd(II)-Mn(III) coprecipitate at pH 7.5.